A Rare Case of Pott’s Disease (Spinal Tuberculosis) Mimicking Metastatic Disease in the Southern Region of Denmark - Osmanagic, Azra (Am J Case Rep, 2016)
Patient: Female, 78 Final Diagnosis: Pott’s disease Symptoms: Back pain • nausea • vomiting • weight loss Medication: — Clinical Procedure: MRI Specialty: Infectious Diseases OBJECTIVE: Rare disease BACKGROUND: Pott’s disease (PD) or spinal tuberculosis is a rare condition which accounts for less than 1% of total tuberculosis (TB) cases. The incidence of PD has recently increased in Europe and the United States, mainly due to immigration; however, it is still a rare diagnosis in Scandinavian countries, and if overlooked it might lead to significant neurologic complications. CASE REPORT: A 78-year-old woman, originally from Eastern Europe, presented to the emergency department with a complaint of nausea, vomiting, weight loss, and severe back pain. On admission she was febrile and had leukocytosis and increased C-reactive protein. Initial spinal x-ray was performed and revealed osteolytic changes in the vertebral body of T11 and T12. Magnetic resonance imaging (MRI) of the spine illustrated spondylitis of T10, T11, and T12, with multiple paravertebral and epidural abscesses, which was suggestive of PD. Polymerase chain reaction (PCR) of the patient’s gastric fluid was positive for Mycobacterium tuberculosis (MT). Based on MRI and PCR findings, standard treatment for TB was initiated. Results of the spine biopsy and culture showed colonies of MT and confirmed the diagnosis afterwards. Due to the instability of the spine and severe and continuous pain, spine-stabilizing surgery was performed. Her TB was cured after nine months of treatment. CONCLUSIONS: PD is an important differential diagnosis of malignancy that should be diagnosed instantly. History of exposure to TB and classic radiologic finding can help make the diagnosis.